Christian Spontaneity and the Clarification of Pleasure - Kendal, Gordon (1982)
Christians are not the only people with reservations about ethical hedonism. But the leading of a Christian life—along the broad lines traced out in the New Testament, say—has often seemed to be particularly disprobative of the theory that the moral end consists in pleasure. And it is not just a theoretical matter: among Christians, pleasure has been ignored, suspected, feared; and only sometimes welcomed. What I shall try to do in this article is examine what substance there is behind this hesitancy, and what significance pleasure should still have in the Christian life. To do this successfully we shall have to clarify the concept of pleasure. This is a task that needs to be done as much for the sake of our moral philosophy as for the sake of our Christianity, and the way in which I shall proceed will be to develop the meaning and the importance of pleasure in close connection with another (and perhaps slightly less controversial) feature of the Christian life: spontaneity. I can anticipate the general drift of the paper here by saying that pleasure, roughly speaking, is felt spontaneity. This has important implications, as does the fact that, for all their doubts about hedonism, Christians have traditionally made use of a number of words not unrelated to ‘pleasure’: words like ‘joy’, ‘contentment’, ‘blessedness’ and ‘happiness’.